Understanding African American's Religious Beliefs and Organ Donation Intentions - Robinson, Dana H. Z. (Journal of religion and health, 2014)
African Americans are overrepresented on the organ transplant waiting list and underrepresented among organ and tissue donors. One of the most highly noted reasons for lack of donation is the perception that donation is contrary to religious beliefs. The purpose of this cross-sectional study is to explore the complexities of religion (beliefs, religiosity, and religious involvement) and its association with willingness to donate and the written expression of donation intentions. Findings from a sample of 505 African American participants suggest that religion is a multidimensional construct and results differ depending on how the construct is measured and operationalized.